2018
DOI: 10.1002/marc.201800140
|View full text |Cite
|
Sign up to set email alerts
|

ICAR ATRP in PEG with Low Concentration of Cu(II) Catalyst: A Versatile Method for Synthesis of Block Copolymer Nanoassemblies under Dispersion Polymerization

Abstract: A versatile method for synthesis of block copolymer nanoassemblies via initiators for continuous activator regeneration (ICAR) atom transfer radical polymerization (ATRP) dispersion polymerization in a low molecular weight poly(ethylene glycol) (PEG) is discussed. This ICAR ATRP dispersion polymerization uses a low concentration of CuBr catalyst, which is stable under atmospheric conditions and is soluble in most polar solvents and employs a polymerization medium of viscous and nonvolatile PEG. Through this IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
(78 reference statements)
0
9
0
1
Order By: Relevance
“…It was believed that the salt-like nature of the ATRP catalyst and the broad MWD were responsible for this drastic difference in nanoparticle morphology. In another study, Zhang and co-workers 89 showed the possibility to prepare well-defined vesicles via ICAR-ATRP. This formulation is based on the chain extension of a PEG macroinitiator with styrene and utilizes PEG as a solvent.…”
Section: Atrpisamentioning
confidence: 99%
“…It was believed that the salt-like nature of the ATRP catalyst and the broad MWD were responsible for this drastic difference in nanoparticle morphology. In another study, Zhang and co-workers 89 showed the possibility to prepare well-defined vesicles via ICAR-ATRP. This formulation is based on the chain extension of a PEG macroinitiator with styrene and utilizes PEG as a solvent.…”
Section: Atrpisamentioning
confidence: 99%
“…[14][15][16] Theoretically,a ny RDRP technique or living polymerization technique can be selected to produce these block copolymer nanoobjects by PISA. Indeed, nitroxide-mediated polymerization (NMP), [14,[17][18][19][20] atom-transfer radical polymerization (ATRP), [21][22][23][24][25][26] Cu-mediated controlled polymerization, [27] iodine-transfer polymerization (ITP), [28] organotellurium-mediated radical polymerization (TERP), [29][30][31] Comediated radical polymerization, [32] ring-opening metathesis polymerization (ROMP), [33][34][35][36] or reversible complexationmediated polymerization (RCMP) [37] have been successfully implemented. However,R AFT-mediated PISA remains the most employed strategy.Inthe above-mentioned first edition of the book in 2008, the pioneering works of Ferguson et al [38] on chain extension of ap reformed poly(acrylic acid) (PAA) macromolecular RAFT (macroRAFT) agent in water with aslow feed of n-butyl acrylate (BA) were the only mention of this strategy,although it was not yet called PISA.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Grundsätzlich kann jede RDRP-Technik oder lebende Polymerisationstechnik verwendet werden, um Blockcopoly-mer-Nanoobjekte mittels PISA herzustellen. Nitroxid-vermittelte Polymerisation (NMP;n itroxide-mediated polymerization), [14,[17][18][19][20] radikalische Atomtransferpolymerisation (ATRP;a tom-transfer radical polymerization) [21][22][23][24][25][26] oder Cuvermittelte kontrollierte Polymerisation, [27,28] Iod-Transfer-Polymerisation (ITP;i odine-transfer polymerization), Organotellur-vermittelte radikalische Polymerisation (TERP; organotellurium-mediated polymerization), [29][30][31] Co-vermittelte radikalische Polymerisation, [32] ringçffnende Metathesepolymerisation (ROMP;r ing-opening methathesis polymerization) [33][34][35][36] oder reversible komplexvermittelte Polymerisation (RCMP;r eversible complexation-mediated polymerization) [37] wurden hierfürb ereits erfolgreich eingesetzt. RAFT-vermittelte PISA ist jedoch die am weitesten verbreitete Strategie.Inder oben erwähnten ersten Buchausgabe aus dem Jahr 2008 waren die Pionierarbeiten von Ferguson et al [38] zur Kettenverlängerung eines makromolekularen Polyacrylsäure(PAA)-RAFT-Agens (MacroRAFT) in Wasser unter langsamer Zufuhr von n-Butylacrylat (BA) die einzige Erwähnung dieser Strategie,die allerdings noch nicht als PISA bezeichnet wurde.S eitdem wird in der überwiegenden Mehrheit der zu PISA durchgeführten Studien RAFT-Polymerisation eingesetzt, was die allgemeine Akzeptanz dieser schnell wachsenden Unterdisziplin bestätigt.…”
Section: Aus Dem Inhaltunclassified